Development and psychometric evaluation of the Persian version of the Phoneme Recognition Test A central auditory processing measure - Shomeil Shushtari, Sahar; Fatahi, Farzaneh; Rouhbakhsh, Nematallah; Saki, Nader; Jalaie, Shohreh; Negin, Ehsan; Tavakoli, Mojtaba; karimi, Majid (Iranian Journal of Child Neurology, 2022)
Objectives The present study evaluating the psychometric properties of the Persian version of the Phoneme Recognition Test (P-PRT) in normal subjects and cochlear implant (CI) users. Material & Methods This study includes developing the Persian phoneme recognition test (PRT), determining its validity and reliability, and comparing the results of a control group versus CI users. The test reliability was examined through a test-retest with an approximately five-week interval. In the present survey, 363 subjects were investigated in three stages. The face validity evaluation stage was conducted on 40 subjects. The psychometric properties of the P-PRT were evaluated in 323 individuals (225 normal subjects and 98 CI users). The test-retest reliability was examined in all the 225 subjects in the control group and 40 CI users. Results The results confirmed the face validity of the P-PRT. No significant differences were observed between the two genders in terms of performance in the P-PRT. Significant differences were observed between the control and CI groups. Evaluating the test-retest reliability suggested perfect reliability (r>0.9) in both groups. Significant differences were observed in the P-PRT between the adults and the 7-year-old subjects compared to other age groups. Conclusion The P-PRT can be used as a valid and reliable test for clinically evaluating phoneme recognition abilities and monitoring the rehabilitation progress